2022
DOI: 10.1109/access.2022.3152779
|View full text |Cite
|
Sign up to set email alerts
|

Novel Variable Switching Frequency PWM Strategy for a SiC-MOSFET-Based Electric Vehicle Inverter to Increase Battery Usage Time

Abstract: In this study, a novel variable switching frequency pulse width modulation (VSFPWM) strategy is proposed to achieve improved electric vehicle inverter efficiency. The silicon carbide (SiC) MOSFET inverter has excellent switching characteristics, thus enabling pulse width modulation control with a high switching frequency. The high switching frequency can reduce the voltage ripples in DC-link capacitors, which enables their use at a reduced capacitance. The switching frequency is typically set to a level that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…In [112], it is shown that a 22.92% reduction in total harmonics distortion (THD) can be achieved by increasing the switching frequency from 10 kHz to 50 kHz using SiC MOSFETs and a double closed-loop vector control on an FPGA controller. Furthermore, in [113] a variable switching frequency strategy during operation is implemented to minimize voltage ripple in the capacitor and switching losses in the inverter.…”
Section: Wideband Controlmentioning
confidence: 99%
“…In [112], it is shown that a 22.92% reduction in total harmonics distortion (THD) can be achieved by increasing the switching frequency from 10 kHz to 50 kHz using SiC MOSFETs and a double closed-loop vector control on an FPGA controller. Furthermore, in [113] a variable switching frequency strategy during operation is implemented to minimize voltage ripple in the capacitor and switching losses in the inverter.…”
Section: Wideband Controlmentioning
confidence: 99%
“…Refs. [112][113][114] explain different variable-frequency PWM strategies and assess the impact of filter elements on network harmonics.…”
Section: Variable-frequency-based Pwmmentioning
confidence: 99%
“…Hình 11. Mạch nghịch lưu và van công suất [6] Hình 12. Vùng làm việc của van Si-IGBT và SiC MOSFET [6] Trong nghiên cứu này, tần số PWM đến 10kHz nên chọn van là Si-IGBT.…”
Section: Chọn Van Công Suất Cho Bộ Inverterunclassified